2013
DOI: 10.1186/1472-6882-13-251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Allium victorialis leaf extracts and its single compounds on aldose reductase, advanced glycation end products and TGF-β1 expression in mesangial cells

Abstract: BackgroundAccumulating evidences suggest that aldose reductase (AR) inhibitors and advanced glycation end product (AGE) formation inhibitors may prevent chronic hyperglycemia-induced long-term complication in diabetes. Transforming growth factor-beta1 (TGF-β1) plays an important role in the development of diabetic nephropathy. Allium species have been utilized in folk medicine throughout the world for the treatment of various physical disorders. However, the benefits of Allium victorialis (A. victorialis) agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Promotes osteoblast differentiation and inhibits osteoclastogenesis, antioxidative, antileishmanial activity, inhibitor of aldose reductase, p90S6 ribosomal kinase (RSK), AP-1 and MAPK signaling, protects mice against fatal anaphylactic shock (Khlebnikov et al, 2007;Cruz et al, 2008;Ding et al, 2010;da Silva et al, 2012;Derewenda et al, 2013;Kim et al, 2013;Satue et al, 2013;Yin et al, 2013) 2015; Kaskoniene et al, 2015b). Oenothein B is comprised of two tellimagrandin I monomers linked between the hexahydroxydiphenoyl groups and the galloyl groups on the glucopyranose ring ( Fig.…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%
“…Promotes osteoblast differentiation and inhibits osteoclastogenesis, antioxidative, antileishmanial activity, inhibitor of aldose reductase, p90S6 ribosomal kinase (RSK), AP-1 and MAPK signaling, protects mice against fatal anaphylactic shock (Khlebnikov et al, 2007;Cruz et al, 2008;Ding et al, 2010;da Silva et al, 2012;Derewenda et al, 2013;Kim et al, 2013;Satue et al, 2013;Yin et al, 2013) 2015; Kaskoniene et al, 2015b). Oenothein B is comprised of two tellimagrandin I monomers linked between the hexahydroxydiphenoyl groups and the galloyl groups on the glucopyranose ring ( Fig.…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%
“…For instance, the use of hexane extracts from the leaves of the plant, Piper auritum , inhibited the formation of AGEs and limited oxidative stress in cell culture and in a murine model of diabetic nephropathy [80]. Similarly, the use of quercetin from leaf extracts of the plant, Allium victorialis , inhibited AGEs formation in cultured mouse kidney mesangial cells [81]. The oral administration of 2-dodecyl-6-methoxycyclohexa-2,5-diene-1,4-dione from the roots of the plant, Averrhoa carambola , has shown to be effective in attenuating AGEs formation and progression of kidney disease in diabetic mice [82].…”
Section: Limiting the Endogenous Formation Of Advanced Glycation End mentioning
confidence: 99%
“…The formation of AGEs occurs as a result of the Maillard reaction, a nonenzymatic modification of proteins, lipids, and nucleic acids by reducing sugars. It has been reported that low‐molecular weight heparin (LMWH; Myint et al, ), a β‐(1,2)‐fructan with branches at O‐6 and terminating with a glucosyl residue (Xiao et al, ), quercitrin (Kim et al, ), and genistein (Jung et al, ) antagonize AGE action on RAGE and have preventive effects on DN. LMWH binds RAGE with an affinity approximately six times higher than AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of AGEs occurs as a result of the Maillard reaction, a nonenzymatic modification of proteins, lipids, and nucleic acids by reducing sugars. It has been reported that lowmolecular weight heparin (LMWH; Myint et al, 2006), a β-(1,2)fructan with branches at O-6 and terminating with a glucosyl residue (Xiao et al, 2013), quercitrin (Kim et al, 2013), and genistein (Jung et al, 2012) Generally speaking, different RAGE ligands induce different signaling pathways in a given type of cell. In accordance with this, cellular biological outcomes are also diverse and at least include hyperproliferation, induction of apoptosis, and increased motility (Sakaguchi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%